ANALISIS TEKNIK PENERJEMAHAN MAJAS IRONI DAN SARKASME DALAM NOVEL THE RETURN OF SHERLOCK HOLMES SERTA DAMPAKNYA TERHADAP KUALITAS TERJEMAHAN - Irene Dinari; Mangatur Nababan; Djatmika Djatmika (PRASASTI: Journal of Linguistics, 2017)
Background: This research is conducted by analyzing figurative language as irony and sarcasm in the novel entitled The Return of Sherlock Holmes (TROSH) and its translation in Bahasa Indonesia. The aims of this research are to (1) identify such types of figurative language as irony and sarcasm in the novel TROSH and its translation in Bahasa Indonesia, (2) identify translation techniques used when translating the irony and sarcasm, (3) find out the translation shifts appearing as effects of the application of the translation techniques, and (4) find out the effects of the translation shifts of irony and sarcasm on translation quality considering accuracy, acceptability, and readability. Method: The method of this study is descriptive qualitative. The source of data is a novel entitled The Return of Sherlock Holmes and its translation. The result of questionnaires from the raters that asses the translations quality also belong to the source of data in this study. The data in this study are phrase, clause, or sentence that contain irony or sarcasm in the novel The Return of Sherlock Holmes. Beside that, the information about the quality of the translation from the raters and informants is also belonged to the data. The technique in conducting the data is done by analysing the document and the questionnaires. Result: The research findings reveal that (1) 67 data of irony and sarcasm are found in the novel The Return of Sherlock Holmes and are divided into 6 subcategories consisting of ironical understatement, non-ironical falsehood, ironical interjections, illocutionary sarcasm, propositional sarcasm, and lexical sarcasm, (2) Several translation techniques employed are established equivalence, modulation, amplification, variation, transposition, linguistic compression, borrowing, reduction, linguistic amplification, compensation, adaptation, and particularization, while some others are couplets, triplets, and quadruplets, (3) the application of the aforementioned translation techniques leads to three possibilities such as the absence of translation shifts of irony and sarcasm, translation shifts to another figurative language, and translation shifts to nonfigurative language, (4) the translation shifts give moderate positive effects on the translation quality of irony and sarcasm found in the novel The Return of Sherlock Holmes with average score of 2.64. Conclustion: Conclusion: The result of this study shows that established equivalence is often used in translating irony and sarcasm. The application of this technique gives a good quality in the translation of irony and sarcasm because that technique can be applied based on the context of situations in the target texts. Meanwhile, established equivalence may give a poor result of the translation quality if it is combined with another technique, for examples: reduction, transposition, and modulation. The impact of the quality is caused by the translation shifting of irony and sarcasm into another figurative language or denotative form. From the analysis of this study, it can be cncluded that the translation shifting of figurative language is one of the important thing in figurative language’s translation and translation quality assessment. Keywords: irony and sarcasm, translation techniques, shift, translation quality